PERANAN EKOWISATA BAGI KESEJAHTERAAN MASYARAKAT BAHOI KECAMATAN LIKUPANG BARAT - Reydi Marco Manahampi; Leonardus R. Rengkung; Yolanda P. I. Rori; Jean F. J. Timban (AGRI-SOSIOEKONOMI, 2015)
This research aims to increasing understanding regarding  the community’s income and level of welfare after the implementation of ecotourism in Bahoi village, Likupang Sub-district, North Minahasa Regency. This research was conducted in 4 months, from May to August 2015. Primary and secondary data was used, and data was collected through interviews. The sampling method used was Purposive Sampling that selected 16 respondents (10%) as the sample, representing of total 160 families that reside in Bahoi village. Analysis shows that ecotourism in Bahoi plays an important role in community life because local community can feels its impact, both directly and indirectly, such as getting additional income, knowledge and experience. Based on this research it can be concluded that ecotourism activities in Bahoi plays a role in increasing the locals' income both directly and indirectly, and ecotourism activities has a positive impact on the welfare of the community and is expected to increase community welfare in Bahoi in general.